PEM electrolysis hydrogen production cathode diffusion layer and preparation method thereof
Patent Information
- Application Number
- CN202310995515.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-08-09
AI Technical Summary
[0006]本发明的目的在于解决目前的PEM电解槽阴极扩散层柔韧性不足的问题,提供了一种具备高机械强度、柔韧性和梯度孔结构的PEM电解制氢阴极扩散层及其制备方法,以满足PEM电解槽在制氢过程中的高效率、稳定性和可靠性要求
[0026]1、经实验验证,制备的石墨烯纤维抗拉强度超700MPa,韧性超过10MJ m-3,电导率超过1*105S/m,表明石墨烯膜具有出色的柔韧性和导电性。
Smart Images

Figure CN117026272B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of renewable energy electrolysis for hydrogen production, and in particular to a PEM electrolysis hydrogen production cathode diffusion layer and its preparation method. Background Technology
[0002] To address the challenges of storing and utilizing renewable energy, water electrolysis for hydrogen production technology has emerged. This technology uses electricity to split water into hydrogen and oxygen, converting renewable energy into hydrogen for clean energy reserves. Proton exchange membrane (PEM) electrolyzers are widely used in water electrolysis for hydrogen production.
[0003] PEM electrolyzers, with their advantages of high efficiency, rapid response, and lightweight design, have become an important technology in hydrogen production. However, PEM electrolyzers typically operate under high or differential pressure conditions, placing high demands on the mechanical strength of the diffusion layer. Currently, titanium felt is the primary material used for the diffusion layer in PEM electrolyzers. While titanium felt possesses excellent mechanical properties, conductivity, and gas-liquid transport performance, its compressibility is very low. Under high or differential pressure conditions at the cathode, the hard titanium material can cause compression and friction damage to the membrane electrode, affecting the lifespan and safety of the membrane electrode and even the electrolyzer. Existing solutions involve adding a piece of carbon paper between the cathode side of the membrane electrode and the titanium felt, utilizing the compression of the carbon paper to buffer the strain caused by high differential pressure conditions. However, this method increases the contact resistance between the diffusion layers, and the friction between the titanium felt and the carbon paper can cause damage and shedding of the carbon paper fibers, affecting its lifespan.
[0004] Therefore, to overcome these problems, developing a cathode diffusion layer that combines flexibility and rigidity is crucial for improving the lifespan and reliability of PEM electrolyzers. This diffusion layer should possess both mechanical strength and flexibility to ensure that the membrane electrode remains undamaged during differential pressure operation. Furthermore, the diffusion layer should exhibit excellent conductivity to accelerate mass transfer and improve hydrogen production efficiency. The diffusion layer is integrally molded, with a tight bond between the flexible layer fibers and the titanium felt fibers, accelerating charge transport and preventing mutual wear.
[0005] Such technological innovation will drive the development of renewable energy, promote the widespread application of water electrolysis for hydrogen production in PEM electrolyzers, and further promote the transformation and sustainable development of clean energy. Summary of the Invention
[0006] The purpose of this invention is to address the problem of insufficient flexibility in the cathode diffusion layer of current PEM electrolyzers. It provides a PEM electrolysis hydrogen production cathode diffusion layer with high mechanical strength, flexibility, and a gradient pore structure, along with its preparation method, to meet the high efficiency, stability, and reliability requirements of PEM electrolyzers in hydrogen production processes. This technological innovation can further promote the development of water electrolysis hydrogen production technology and facilitate the utilization of renewable energy and the transition to clean energy.
[0007] To achieve the above objectives, the technical solution provided by the present invention is as follows: a PEM electrolysis hydrogen production cathode diffusion layer, comprising a titanium felt, wherein a graphene film is prepared in situ on the titanium felt as a buffer layer, so that the diffusion layer has both high mechanical strength and flexibility, and by changing the diameter of the graphene fibers in the graphene film, the diffusion layer forms a gradient pore structure, thereby accelerating the gas-liquid transport speed.
[0008] Preferably, the diameter of graphene fibers can be changed by controlling the slurry concentration, voltage, and flow rate parameters during the graphene electrospinning process.
[0009] Preferably, the diameter of the graphene fiber is in the range of 3-10 micrometers.
[0010] This invention also provides a method for preparing the above-mentioned PEM electrolysis hydrogen production cathode diffusion layer, comprising the following steps:
[0011] 1) Preparation of graphene oxide slurry
[0012] Natural graphite was treated using a modified Staudenmaier method: concentrated sulfuric acid and concentrated nitric acid were mixed in an ice-water bath, and then natural graphite was added. The mixture was stirred at room temperature, and deionized water was added to terminate the oxidation process. The resulting suspension was then repeatedly washed with water and hydrochloric acid solution to remove residual chemicals and impurities. Finally, the suspension was centrifuged to a preset pH value to obtain treated graphite. The treated graphite was then subjected to ultrasonic treatment in an ice bath to obtain exfoliated graphene oxide nanosheets. The dispersion was then concentrated to the desired concentration using rotary evaporation to obtain graphene oxide slurry. Finally, a polymer thickener was used to regulate the rheological properties of the graphene oxide slurry, giving it stretchability so that it could be electrospun.
[0013] 2) Electrospinning of graphene oxide
[0014] A titanium felt with its oxide layer removed and cleaned and dried is used as the receiver of an electrospinning machine. The propulsion speed of the feed pump and the electrostatic field voltage are controlled to obtain graphene fibers of the desired diameter. Increasing the voltage or decreasing the flow rate can decrease the fiber diameter, while decreasing the voltage or increasing the flow rate will increase the fiber diameter. As the spinning time increases, the graphene oxide fibers gradually accumulate on the titanium felt to form a film, resulting in a graphene oxide film / titanium felt. The thickness of the graphene oxide film can be adjusted by controlling the time.
[0015] 3) Reduction of graphene oxide film
[0016] The graphene oxide film / titanium felt obtained in step 2) is immersed in a sealed container containing hydroiodic acid solution. It is first treated at low temperature for a preset time, then treated at high temperature for a preset time, and then cooled to room temperature. It is repeatedly washed with pure water and anhydrous ethanol to remove residual iodine ions and iodine. After vacuum drying, a reduced graphene film / titanium felt is obtained. The reduced graphene film / titanium felt is subjected to hot pressing to make the fibers overlap more tightly, and a graphene film / titanium felt blank is obtained.
[0017] 4) Vacuum sintering
[0018] The graphene film / titanium felt blank obtained in step 3) is placed in a vacuum sintering furnace for vacuum sintering, so that the titanium felt fiber and graphene fiber are more tightly bonded, and the preparation is completed.
[0019] Preferably, in step 1), the concentration of the concentrated sulfuric acid is 98%, the concentration of the concentrated nitric acid is 68%, and the volume ratio of the two is 7:4; the particle size of the natural graphite is 200-500 mesh; centrifugation is performed until the pH value is close to 7; and the dispersion is concentrated to the desired concentration of 15-30 mg / ml using rotary evaporation.
[0020] Preferably, in step 1), the polymer thickener is one or more combinations of sodium polyacrylate, polyvinyl alcohol, and PVDF with a molecular weight greater than or equal to 1 million.
[0021] Preferably, in step 2), by controlling the parameters, a layer of graphene oxide film with a large fiber diameter and the smallest pore size is first spun on the titanium felt; then the voltage is increased, and another layer of graphene oxide film with a smaller fiber diameter and a larger pore size is spun. This process is repeated several times to form a multilayer graphene oxide film with an increasing average pore size gradient on the titanium felt. This will help the hydrogen bubbles generated on the membrane electrode to pass through the continuous through-holes with a decreasing pore size gradient under pressure. According to the Bernoulli effect, the gas flow rate will gradually increase, thereby accelerating the gas escape and reducing the time that the gas occupies the active sites of the catalyst, thus improving the electrolysis efficiency.
[0022] Preferably, in step 2), the titanium felt has a thickness of 200 micrometers and a fiber diameter of 50 micrometers; the propulsion pump has a propulsion speed of 0.1-0.5 ml / min; the electrostatic field voltage is 10-30 kV; and the single-layer graphene oxide film has a thickness of 30-100 micrometers and has 3-8 layers.
[0023] Preferably, in step 3), the graphene oxide film / titanium felt is immersed in a sealed container containing 10 wt% hydroiodic acid solution, first treated at a low temperature of 5°C for 8 hours, and then treated at a high temperature of 90°C for 1 hour; the vacuum drying temperature is 60°C and the time is 48 hours.
[0024] Preferably, in step 4), the temperature of the vacuum sintering is 1000-1300℃.
[0025] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0026] 1. Experimental verification shows that the prepared graphene fibers have a tensile strength exceeding 700 MPa and a toughness exceeding 10 MJ / m. -3 Electrical conductivity exceeding 1*10 5 The S / m ratio indicates that the graphene film has excellent flexibility and conductivity.
[0027] 2. The graphene film is formed in situ on the titanium felt and bonded tightly after sintering, which greatly reduces the contact resistance and has better conductivity than the combination of titanium felt and carbon paper. At the same time, it avoids friction between the titanium felt and the buffer layer, which greatly improves the life of the diffusion layer.
[0028] 3. The gradient pore structure accelerates hydrogen diffusion, reduces the ohmic resistance of bubbles, and improves electrolysis efficiency. Attached Figure Description
[0029] Figure 1 This is a flowchart of the diffusion layer preparation process in Example 1.
[0030] Figure 2 The image shows a product photograph of the diffusion layer in Example 1. In the figure, (a) is the titanium felt side and (b) is the graphene film side.
[0031] Figure 3 The image shows an optical micrograph of the diffusion layer in Example 1. In the image, (a) is the titanium felt side, (b) is the graphene film side, and (c) is a cross-section.
[0032] Figure 4 This figure compares the water electrolysis performance of a PEM electrolyzer assembled using the diffusion layer prepared according to the present invention with that of a conventional diffusion layer. Detailed Implementation
[0033] The present invention will be further described below with reference to specific embodiments.
[0034] Example 1
[0035] 1) Preparation of graphene oxide slurry
[0036] A modified Staudenmaier process was used to process natural graphite: A graphene oxide slurry was prepared using 300-mesh natural graphite. 140 ml of concentrated sulfuric acid (98%), 80 ml of concentrated nitric acid (68%), and 10 g of natural graphite were carefully mixed in an ice-water bath at a volume ratio of 7:4. Natural graphite was then added to the mixture, and the mixture was stirred at room temperature for 100 hours. After terminating the oxidation process with deionized water, the resulting suspension was repeatedly washed with water and hydrochloric acid (HCl) to remove residual chemicals and impurities. Finally, the suspension was centrifuged until the pH was close to 7. The resulting nanosheets were ultrasonically treated in an ice bath for 1 hour to obtain exfoliated graphene oxide nanosheets, which were then rotary evaporated to a suspension concentration of 25 mg / ml. Polymer thickeners are used to regulate the rheological properties of the slurry, giving it stretchability and enabling it to be electrospun. The selected polymer thickener is sodium ultra-high molecular weight polyacrylate (molecular weight 1 million), which is prepared into a solution with a concentration of 25 mg / ml. The graphene oxide suspension and the polymer thickener solution are mixed evenly in equal volumes.
[0037] 2) Electrospinning of graphene oxide
[0038] like Figure 1 As shown, a titanium felt (200 micrometers thick, 50 micrometers fiber diameter) that has had its oxide layer removed and has been cleaned and dried is used as the receiver of the electrospinning machine. The ambient temperature and humidity of the electrospinning machine are controlled at 60℃ / 10%, and the speed of the electrospinning push pump (slurry flow rate) is 0.3 ml / min. The electrostatic field voltage between the capillary needle and the titanium felt was initially set to 15 kV and run for 20 minutes. A layer of graphene oxide film with a larger fiber diameter (smallest pore size) was first spun on the titanium felt. The voltage was then increased to 20 kV and run for 20 minutes to obtain a graphene oxide film with a fiber diameter smaller than the first layer and a pore size slightly larger than the first layer. The voltage was then further increased to 25 kV and run for 20 minutes to obtain an outermost layer of graphene oxide film with a fiber diameter smaller than the second layer and a pore size slightly larger than the second layer. This process can form a three-layer graphene oxide film with an increasing average pore size gradient on the titanium felt, resulting in a graphene oxide film / titanium felt. Under pressure, hydrogen bubbles generated on the membrane electrode pass through continuous through-holes with decreasing pore size gradient. According to the Bernoulli effect, the gas flow rate gradually increases, thereby accelerating gas escape and reducing the time that the gas occupies the active sites of the catalyst, thus improving the electrolysis efficiency.
[0039] 3) Reduction of graphene oxide film
[0040] The graphene oxide film / titanium felt obtained in step 2) was immersed in a sealed container containing hydroiodic acid solution (HI, 10 wt%), first treated at 5°C for 8 hours, then treated at 90°C for 1 hour, cooled to room temperature, and repeatedly washed with pure water and anhydrous ethanol to remove residual iodine ions and iodine, and vacuum dried at 60°C for 48 hours to obtain the reduced graphene film / titanium felt. The reduced graphene film / titanium felt was subjected to hot pressing treatment to make the fiber overlap tighter, and the graphene film / titanium felt blank was obtained.
[0041] 4) Vacuum sintering
[0042] The graphene film / titanium felt preform obtained in step 3) was placed in a vacuum sintering furnace and sintered at 1200℃ to make the titanium felt fibers and graphene fibers more tightly bonded. The resulting PEM electrolytic hydrogen production cathode diffusion layer with high mechanical strength, flexibility, and gradient pore structure is shown in the figure. Figure 2 As shown. The surface morphology was observed using a digital optical microscope, as shown. Figure 3 As shown in the figure, (a) is the titanium felt side, showing the porous felt structure woven from titanium fibers; (b) is the graphene film side (i.e., the buffer layer side), showing the porous structure formed by the stacking of graphene fibers; (c) is a cross-sectional photograph, showing that the graphene film and titanium felt are tightly bonded and have a smooth surface.
[0043] Example 2
[0044] 1) Preparation of graphene oxide slurry
[0045] A modified Staudenmaier process was used to process natural graphite: A graphene oxide slurry was prepared using 200-mesh natural graphite. 140 ml of concentrated sulfuric acid (98%), 80 ml of concentrated nitric acid (68%), and 10 g of natural graphite were carefully mixed in an ice-water bath at a volume ratio of 7:4. Natural graphite was then added to the mixture, and the mixture was stirred at room temperature for 100 hours. After adding deionized water to terminate the oxidation process, the resulting suspension was repeatedly washed with water and hydrochloric acid (HCl) solution to remove residual chemicals and impurities. Finally, the suspension was centrifuged until the pH value was close to 7. The resulting nanosheets were ultrasonically treated in an ice bath for 1 hour to obtain exfoliated graphene oxide nanosheets, which were then rotary evaporated to a suspension concentration of 15 mg / ml. Polymer thickeners are used to regulate the rheological properties of the slurry, giving it stretchability and enabling it to be electrospun. The selected polymer thickeners are sodium ultra-high molecular weight polyacrylate (molecular weight 1 million) and polyvinyl alcohol (molecular weight 2 million), with a mass ratio of 2:1, and are prepared into a solution with a concentration of 15 mg / ml. The graphene oxide suspension and the polymer thickener solution are mixed evenly in equal volumes.
[0046] 2) Electrospinning of graphene oxide
[0047] like Figure 1 As shown, a titanium felt (200 micrometers thick, 50 micrometers fiber diameter) that has had its oxide layer removed and has been cleaned and dried is used as the receiver of the electrospinning machine. The ambient temperature and humidity of the electrospinning machine are controlled at 60℃ / 10%, and the speed of the electrospinning push pump (slurry flow rate) is 0.5 ml / min. The electrostatic field voltage between the capillary needle and the titanium felt was initially set to 10 kV and run for 20 minutes. A layer of graphene oxide film with a larger fiber diameter (smallest pore size) was first spun on the titanium felt. The voltage was then increased to 15 kV and run for 20 minutes to obtain a graphene oxide film with a fiber diameter smaller than the first layer and a pore size slightly larger than the first layer. The voltage was then further increased to 20 kV and run for 20 minutes to obtain an outermost layer of graphene oxide film with a fiber diameter smaller than the second layer and a pore size slightly larger than the second layer. This process can form a three-layer graphene oxide film with an increasing average pore size gradient on the titanium felt, resulting in a graphene oxide film / titanium felt. Under pressure, hydrogen bubbles generated on the membrane electrode pass through continuous through-holes with decreasing pore size gradient. According to the Bernoulli effect, the gas flow rate gradually increases, thereby accelerating gas escape and reducing the time that the gas occupies the active sites of the catalyst, thus improving the electrolysis efficiency.
[0048] 3) Reduction of graphene oxide film
[0049] The graphene oxide film / titanium felt obtained in step 2) was immersed in a sealed container containing hydroiodic acid solution (HI, 10 wt%), first treated at 5°C for 8 hours, then treated at 90°C for 1 hour, cooled to room temperature, and repeatedly washed with pure water and anhydrous ethanol to remove residual iodine ions and iodine, and vacuum dried at 60°C for 48 hours to obtain the reduced graphene film / titanium felt. The reduced graphene film / titanium felt was subjected to hot pressing treatment to make the fiber overlap tighter, and the graphene film / titanium felt blank was obtained.
[0050] 4) Vacuum sintering
[0051] The graphene film / titanium felt blank obtained in step 3) is placed in a vacuum sintering furnace and sintered at 1000℃ to make the titanium felt fiber and graphene fiber more tightly bonded.
[0052] Example 3
[0053] 1) Preparation of graphene oxide slurry
[0054] A modified Staudenmaier process was used to process natural graphite: A graphene oxide slurry was prepared using 500-mesh natural graphite. 140 ml of concentrated sulfuric acid (98%), 80 ml of concentrated nitric acid (68%), and 10 g of natural graphite were carefully mixed in an ice-water bath at a volume ratio of 7:4. Natural graphite was then added to the mixture, and the mixture was stirred at room temperature for 100 hours. After terminating the oxidation process with deionized water, the resulting suspension was repeatedly washed with water and hydrochloric acid (HCl) solution to remove residual chemicals and impurities. Finally, the suspension was centrifuged until the pH value was close to 7. The resulting nanosheets were ultrasonically treated in an ice bath for 1 hour to obtain exfoliated graphene oxide nanosheets, which were then rotary evaporated to a suspension concentration of 30 mg / ml. Polymer thickeners are used to regulate the rheological properties of the slurry, giving it stretchability and enabling it to be electrospun. The selected polymer thickeners are sodium ultra-high molecular weight polyacrylate (molecular weight 1 million) and PVDF (molecular weight 1 million), with a mass ratio of 1:1, and are prepared into a solution with a concentration of 30 mg / ml. The graphene oxide suspension and the polymer thickener solution are mixed evenly in equal volumes.
[0055] 2) Electrospinning of graphene oxide
[0056] like Figure 1 As shown, a piece of titanium felt (200 micrometers thick, 50 micrometers fiber diameter) that has had its oxide layer removed and has been cleaned and dried is used as the receiver of the electrospinning machine. The ambient temperature and humidity of the electrospinning machine are controlled at 60℃ / 10%, and the speed of the electrospinning push pump (slurry flow rate) is 0.1 ml / min. The electrostatic field voltage between the capillary needle and the titanium felt was initially set to 20 kV and run for 20 minutes. A layer of graphene oxide film with a larger fiber diameter (smallest pore size) was first spun on the titanium felt. The voltage was then increased to 25 kV and run for 20 minutes to obtain a graphene oxide film with a fiber diameter smaller than the first layer and a pore size slightly larger than the first layer. The voltage was then further increased to 30 kV and run for 20 minutes to obtain an outermost layer of graphene oxide film with a fiber diameter smaller than the second layer and a pore size slightly larger than the second layer. This process can form a three-layer graphene oxide film with an increasing average pore size gradient on the titanium felt, resulting in a graphene oxide film / titanium felt. Under pressure, hydrogen bubbles generated on the membrane electrode pass through continuous through-holes with decreasing pore size gradient. According to the Bernoulli effect, the gas flow rate gradually increases, thereby accelerating gas escape and reducing the time that the gas occupies the active sites of the catalyst, thus improving the electrolysis efficiency.
[0057] 3) Reduction of graphene oxide film
[0058] The graphene oxide film / titanium felt obtained in step 2) was immersed in a sealed container containing hydroiodic acid solution (HI, 10 wt%), first treated at 5°C for 8 hours, then treated at 90°C for 1 hour, cooled to room temperature, and repeatedly washed with pure water and anhydrous ethanol to remove residual iodine ions and iodine, and vacuum dried at 60°C for 48 hours to obtain the reduced graphene film / titanium felt. The reduced graphene film / titanium felt was subjected to hot pressing treatment to make the fiber overlap tighter, and the graphene film / titanium felt blank was obtained.
[0059] 4) Vacuum sintering
[0060] The graphene film / titanium felt blank obtained in step 3) is placed in a vacuum sintering furnace and sintered at 1300℃ to make the titanium felt fiber and graphene fiber more tightly bonded.
[0061] Comparative Example 1
[0062] The cathode diffusion layers of the conventional titanium felt + carbon paper, and those of Examples 1, 2, and 3, were evaluated sequentially using a PEM electrolytic cell with an active area of 50*50mm. The membrane electrode used was a Chemours N117 membrane, and the anode iridium loading was 1 mg / cm³. 2 The cathode platinum loading is 0.3 mg / cm³. 2 The conductivity of pure water is <0.1 μS / cm, the tightening torque of the electrolytic cell is 5 Nm, and the operating temperature is 60℃. For example... Figure 4 As shown, the electrolyzer performance using the diffusion layers in Examples 1, 2, and 3 significantly surpasses that of the traditional titanium felt + carbon paper combination. This indicates that the PEM electrolytic hydrogen production cathode diffusion layer proposed in this invention has higher conductivity and can improve electrolysis efficiency. This is attributed to the in-situ growth of the graphene film as a buffer layer on the titanium felt, resulting in a tight bond, and the graphene fibers possess ultra-high conductivity. The resistance and compressibility of Examples 1, 2, and 3, and the titanium felt + carbon paper combination were tested, and the results are shown in Table 1.
[0063] Table 1. Comparison of resistance and compressibility between Examples 1, 2, and 3 and the carbon paper + titanium felt combination.
[0064]
[0065] As shown in Table 1, the resistance of Examples 1, 2, and 3 is an order of magnitude lower than that of the titanium felt + carbon paper combination, indicating that the product of the present invention has better conductivity. The compression ratio of Examples 1, 2, and 3 under different pressures is slightly higher than that of the titanium felt + carbon paper combination, indicating that the product of the present invention has a buffering effect that exceeds that of carbon paper.
[0066] The above-described embodiments are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Therefore, any changes made in accordance with the shape and principle of the present invention should be covered within the protection scope of the present invention.
Claims
1. A PEM electrolytic hydrogen production cathode diffusion layer, comprising a titanium felt, characterized in that, Graphene films were prepared in situ on titanium felt as buffer layers, and the diffusion layer was made into a gradient pore structure by changing the diameter of the graphene fibers in the graphene film. The method for preparing the diffusion layer of the PEM electrolysis hydrogen production cathode includes the following steps: 1) Preparation of graphene oxide slurry; Natural graphite was treated using a modified Staudenmaier method: concentrated sulfuric acid and concentrated nitric acid were mixed in an ice-water bath, and then natural graphite was added. The mixture was stirred at room temperature, and deionized water was added to terminate the oxidation process. The resulting suspension was then repeatedly washed with water and hydrochloric acid solution to remove residual chemicals and impurities. Finally, the suspension was centrifuged to a preset pH value to obtain treated graphite. The treated graphite was then subjected to ultrasonic treatment in an ice bath to obtain exfoliated graphene oxide nanosheets. The dispersion was then concentrated to the desired concentration using rotary evaporation to obtain graphene oxide slurry. Finally, a polymer thickener was used to regulate the rheological properties of the graphene oxide slurry. The polymer thickener is one or more of sodium polyacrylate, polyvinyl alcohol, and PVDF with a molecular weight greater than or equal to 1 million. 2) Electrospinning of graphene oxide; A titanium felt with its oxide layer removed and cleaned and dried is used as the receiver of an electrospinning machine. The propulsion speed of the feed pump and the electrostatic field voltage are controlled to obtain graphene fibers of the desired diameter. As the spinning time increases, the graphene oxide fibers gradually accumulate on the titanium felt to form a film, resulting in a graphene oxide film / titanium felt. The thickness of the graphene oxide film can be adjusted by controlling the time. By controlling the parameters, a layer of graphene oxide film with large fiber diameter and small pore size is first spun on the titanium felt; then the voltage is increased to continue spinning a layer of graphene oxide film with a smaller fiber diameter and larger pore size than the previous layer. This process is repeated several times to form a multilayer graphene oxide film with an increasing average pore size gradient on the titanium felt. 3) Reduction of graphene oxide film; The graphene oxide film / titanium felt obtained in step 2) is immersed in a sealed container containing hydroiodic acid solution. It is first treated at low temperature for a preset time, then treated at high temperature for a preset time, and then cooled to room temperature. It is repeatedly washed with pure water and anhydrous ethanol to remove residual iodine ions and iodine. After vacuum drying, a reduced graphene film / titanium felt is obtained. The reduced graphene film / titanium felt is subjected to hot pressing to make the fibers overlap more tightly, and a graphene film / titanium felt blank is obtained. 4) Vacuum sintering; The graphene film / titanium felt blank obtained in step 3) is placed in a vacuum sintering furnace for vacuum sintering to make the titanium felt fiber and graphene fiber more tightly bonded, thus completing the preparation; wherein, the vacuum sintering temperature is 1000-1300℃.
2. The PEM electrolysis hydrogen production cathode diffusion layer according to claim 1, characterized in that, The diameter of the graphene fibers ranges from 3 to 10 micrometers.
3. The PEM electrolysis hydrogen production cathode diffusion layer according to claim 1, characterized in that, In step 1), the concentration of the concentrated sulfuric acid is 98%, the concentration of the concentrated nitric acid is 68%, and the volume ratio of the two is 7:4; the particle size of the natural graphite is 200-500 mesh; centrifugation is performed until the pH value is close to 7; and the dispersion is concentrated to the required concentration of 15-30 mg / ml using rotary evaporation.
4. The PEM electrolysis hydrogen production cathode diffusion layer according to claim 1, characterized in that, In step 2), the titanium felt has a thickness of 200 micrometers and a fiber diameter of 50 micrometers; the propulsion pump has a propulsion speed of 0.1-0.5 ml / min; the electrostatic field voltage is 10-30 kV; the single-layer graphene oxide film has a thickness of 30-100 micrometers and has 3-8 layers.
5. The PEM electrolysis hydrogen production cathode diffusion layer according to claim 1, characterized in that, In step 3), the graphene oxide film / titanium felt is immersed in a sealed container containing 10wt% hydroiodic acid solution, first treated at a low temperature of 5°C for 8 hours, and then treated at a high temperature of 90°C for 1 hour; the vacuum drying temperature is 60°C and the time is 48 hours.